Facilitating the transition of young people with long-term conditions through health services from childhood to adulthood: the Transition research programme - Allan Colver; Tim Rapley; Jeremy R Parr; Helen McConachie; Gail Dovey-Pearce; Ann Le Couteur; Janet E McDonagh; Caroline Bennett; Jennifer Hislop; Gregory Maniatopoulos; Kay D Mann; Hannah Merrick; et al. (NIHR Journals Library, 2019)
Background: As young people with long-term conditions move from childhood to adulthood, their health may deteriorate and their social participation may reduce. 'Transition' is the 'process' that addresses the medical, psychosocial and educational needs of young people during this time. 'Transfer' is the 'event' when medical care moves from children's to adults' services. In a typical NHS Trust serving a population of 270,000, approximately 100 young people with long-term conditions requiring secondary care reach the age of 16 years each year. As transition extends over about 7 years, the number in transition at any time is approximately 700. Objectives: Purpose - to promote the health and well-being of young people with long-term conditions by generating evidence to enable NHS commissioners and providers to facilitate successful health-care transition. Objectives - (1) to work with young people to determine what is important in their transitional health care, (2) to identify the effective and efficient features of transitional health care and (3) to determine how transitional health care should be commissioned and provided. Design, settings and participants: Three work packages addressed each objective. Objective 1. (i) A young people's advisory group met monthly throughout the programme. (ii) It explored the usefulness of patient-held health information. (iii) A 'Q-sort' study examined how young people approached transitional health care. Objective 2. (i) We followed, for 3 years, 374 young people with type 1 diabetes mellitus (150 from five sites in England), autism spectrum disorder (118 from four sites in England) or cerebral palsy (106 from 18 sites in England and Northern Ireland). We assessed whether or not nine proposed beneficial features (PBFs) of transitional health care predicted better outcomes. (ii) We interviewed a subset of 13 young people about their transition. (iii) We undertook a discrete choice experiment and examined the efficiency of illustrative models of transition. Objective 3. (i) We interviewed staff and observed meetings in three trusts to identify the facilitators of and barriers to introducing developmentally appropriate health care (DAH). We developed a toolkit to assist the introduction of DAH. (ii) We undertook a literature review, interviews and site visits to identify the facilitators of and barriers to commissioning transitional health care. (iii) We synthesised learning on 'what' and 'how' to commission, drawing on meetings with commissioners. Main outcome measures: Participation in life situations, mental well-being, satisfaction with services and condition-specific outcomes. Strengths: This was a longitudinal study with a large sample; the conditions chosen were representative; non-participation and attrition appeared unlikely to introduce bias; the research on commissioning was novel; and a young person's group was involved. Limitations: There is uncertainty about whether or not the regions and trusts in the longitudinal study were representative; however, we recruited from 27 trusts widely spread over England and Northern Ireland, which varied greatly in the number and variety of the PBFs they offered. The quality of delivery of each PBF was not assessed. Owing to the nature of the data, only exploratory rather than strict economic modelling was undertaken. Results and conclusions: (1) Commissioners and providers regarded transition as the responsibility of children's services. This is inappropriate, given that transition extends to approximately the age of 24 years. Our findings indicate an important role for commissioners of adults' services to commission transitional health care, in addition to commissioners of children's services with whom responsibility for transitional health care currently lies. (2) DAH is a crucial aspect of transitional health care. Our findings indicate the importance of health services being commissioned to ensure that providers deliver DAH across all health-care services, and that this will be facilitated by commitment from senior provider and commissioner leaders. (3) Good practice led by enthusiasts rarely generalised to other specialties or to adults' services. This indicates the importance of NHS Trusts adopting a trust-wide approach to implementation of transitional health care. (4) Adults' and children's services were often not joined up. This indicates the importance of adults' clinicians, children's clinicians and general practitioners planning transition procedures together. (5) Young people adopted one of four broad interaction styles during transition: 'laid back', 'anxious', 'wanting autonomy' or 'socially oriented'. Identifying a young person's style would help personalise communication with them. (6) Three PBFs of transitional health care were significantly associated with better outcomes: 'parental involvement, suiting parent and young person', 'promotion of a young person's confidence in managing their health' and 'meeting the adult team before transfer'. (7) Maximal service uptake would be achieved by services encouraging appropriate parental involvement with young people to make decisions about their care. A service involving 'appropriate parental involvement' and 'promotion of confidence in managing one's health' may offer good value for money. Future work: How might the programme's findings be implemented by commissioners and health-care providers? What are the most effective ways for primary health care to assist transition and support young people after transfer? Study registration: This study is registered as UKCRN 12201, UKCRN 12980, UKCRN 12731 and UKCRN 15160. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.